Pengembangan Buku Ajar “Pengantar Aljabar” Berorientasi Pada High Order Thinking (HOTS) - Hanim Faizah; Nur Fathonah (Universitas Mathla'ul Anwar Banten, 2021)
In Elementer Algebra courses, the students have not been trained to solve problems that are classified in HOTS problems. Therefore, it is need to develop a teaching book that can help students to develop High Order Thinking Skill. This research aims to develop a teaching book entitled